THE EFFECT OF SERVICE DIGITALIZATION AND EMPLOYEE COMPETENCE ON EMPLOYEE PERFORMANCE WITH DIGITAL LITERACY AS A MODERATING VARIABLE AT THE BANDAR LAMPUNG MEDIUM TAX SERVICE OFFICE - Indra, Heries; Haninun, Haninun; Dunan, Hendri (PT. Hasba Edukasi Mandiri, 2026)
Digital transformation in tax administration has reshaped service systems, business processes, and employees’ work patterns, requiring both effective digital technologies and appropriate employee competencies and digital literacy. This study examines the effects of service digitalization and employee competence on employee performance and the moderating role of digital literacy at the Bandar Lampung Medium Tax Office. A quantitative explanatory approach was applied to 58 employees using a saturated sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using PLS-SEM with SmartPLS 4 and bootstrapping at a 5% significance level. The results show that service digitalization positively and significantly affects employee performance (β = 0.324; p = 0.0055), while employee competence has a stronger positive and significant effect (β = 0.431; p < 0.001). Digital literacy does not significantly moderate the relationship between service digitalization and performance (β = 0.186; p = 0.1048), but significantly strengthens the effect of employee competence on performance (β = 0.380; p = 0.0016). The model explains 65.90% of the variance in employee performance. These findings highlight the importance of effective technology utilization, continuous competency development, and strengthening digital literacy in supporting employee performance in digital tax administration.